2020
DOI: 10.1128/jvi.00710-20
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Adenovirus Replication by the Importin α/β1 Nuclear Import Inhibitor Ivermectin

Abstract: Human adenoviruses (HAdV) are ubiquitous within the human population and comprise a significant burden of respiratory illnesses worldwide. Pediatric and immunocompromised individuals are at particular risk for developing severe disease, however, no approved antiviral therapies specific to HAdV exist. Ivermectin is an FDA-approved broad spectrum antiparasitic drug that also exhibits antiviral properties against a diverse range of viruses. Its proposed function is inhibiting the classical protein nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 74 publications
1
37
0
Order By: Relevance
“…Previously, for other RNA viruses, Ivermectin acted on targets such as Importin-α-mediated nuclear import of viral proteins (Yang et al, 2020 ) and Helicase (Mastrangelo et al, 2012 ). Inhibition of the Importin-α/β1 nuclear import pathway by targeting Importin-α has been reported to be the mode of action of Ivermectin (Atkinson et al, 2018 ; King et al, 2020 ; Shechter et al, 2017 ; Wagstaff et al, 2011 ; 2012 ; Yang et al, 2020 ). In this study, the identification of RdRp as a potential target for Ivermectin for SARS-COV-2 would certainly bring more opportunities to resist this virus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, for other RNA viruses, Ivermectin acted on targets such as Importin-α-mediated nuclear import of viral proteins (Yang et al, 2020 ) and Helicase (Mastrangelo et al, 2012 ). Inhibition of the Importin-α/β1 nuclear import pathway by targeting Importin-α has been reported to be the mode of action of Ivermectin (Atkinson et al, 2018 ; King et al, 2020 ; Shechter et al, 2017 ; Wagstaff et al, 2011 ; 2012 ; Yang et al, 2020 ). In this study, the identification of RdRp as a potential target for Ivermectin for SARS-COV-2 would certainly bring more opportunities to resist this virus.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established from earlier (Atkinson et al, 2018 ; Shechter et al, 2017 ; Wagstaff et al, 2011 ; 2012 ) as well as recent (King et al, 2020 ; Yang et al, 2020 ) experimental studies that Ivermectin binds to Importin-α and not to Importin-β1; inhibition of Importin-α leads to the inhibition of Importin-α/β1 interaction. Thus, in this study, we have used the crystal structure of human Importin-α with the highest resolution and not that of Importin-α/β1 to know the inhibition capability of Ivermectin as the binding site of Ivermectin is present in Importin-α and not in Importin-β1 (Wagstaff et al, 2012 ; Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Consistent with the fact that many viruses are known to rely on IMPα/β1-dependent nuclear import of specific viral proteins for robust infection [14,27,28], ivermectin has been confirmed in a body of in vitro studies to be active in limiting infection by a range of different RNA viruses [10,14], including HIV-1 [7], DENV (all four serotypes) and related flaviviruses [8,11,12], influenza, and alphaviruses such as Venezuelan equine encephalitis virus (VEEV) and chikungunya [9,15,16] (see Table 1); it is also active against DNA viruses [18][19][20]. Recent studies indicate it is a potent inhibitor of SARS-CoV-2 [17].…”
Section: Ivermectin As An Antiviralmentioning
confidence: 98%
“…Tazarotene, a selective agonist of the retinoic acid receptor β (RARβ), was investigated in another study as a HAdV replication inhibitor after the transcriptomic analysis of infected A549 cells revealed that the virus induced the downregulation of RARβ mRNA [ 137 ]. Very recently, ivermectin was found to inhibit gene transcription, protein expression, genome replication, and viral progeny production of HAdV-5 and the more clinically relevant HAdV-3 [ 138 ]. Ivermectin disrupted the binding of the E1A protein to importin-α, preventing E1A import into the nucleus.…”
Section: Discovery Of New Antiviral Therapiesmentioning
confidence: 99%